Pendekatan Model Pemahaman Keagamaan: Tekstual Dan Kontekstual Inklusif Dan Eksklusif - Siti Asiyah; Hamdanah Hamdanah (Journal on Education, 2024)
A model approach to religious understanding is important in approaching sacred texts and the values ​​contained therein. In this article, four main approaches to uncovering the meaning of religious texts are discussed: textual, contextual, inclusive, and exclusive approaches. Each approach has its own characteristics that impact religious interpretation and practice. Factors such as education, personal experience, and social context influence the selection of approaches by scholars, religious practitioners, and communities of faith. The interaction between textual and contextual approaches can complement or conflict with each other in analyzing religious texts. An inclusive approach supports interreligious dialogue, tolerance and cross-cultural understanding in the context of globalization, while an exclusive approach can have complex implications for religious pluralism and human rights.